A study on greenish pattern of Indian consumers with special reference to their plastic bag usage behavior - Madan Mohan, G.; Prabhu, M.; Abdullah, Nabaz Nawzad (Business: Theory and Practice, 2021)
The Population explosion has led to excessive consumption and exploitation of natural resources resulting in degradation of the biophysical environment. Many agitations have gained momentum in various parts of the world to protect it from environmental degradation. Many governments have banned the usage of plastics in their endeavor to protect the environment. This descriptive research has attempted to study the greenish pattern of 320 Indian consumers with special reference to their plastic bag usage behavior while carrying their purchases back home. The Results of the study have revealed that customers accord importance to the environmental impact of goods and services before purchasing such goods and they prefer to visit shops that are eco-friendly while they do not attach much importance to the environmental reputation of companies dealing with such goods and services. They prefer green products due to their good quality and reliability and are willing to pay a premium price for such products.